The Effect of Capital Structure and Intangible Asset Contribution to Company Value Moderated by Managerial Ownership - Ika Ismiyar; Riris Rotua Sitorus (Jurnal Syntax Transformation, 2024)
The purpose of this study is to examine how competently the impact of capital structure and intangible assets on the value of companies moderated by managerial ownership. The views in this study use secondary data sourced from the annual reports of companies in the consumer goods industry sector for 2018 - 2022 with a sample of 110 company data will then be examined using the eviews 12 statistical test. The results of data testing state that capital structure negatively affects the value of the company. Intangible assets have no effect on the value of the company. Managerial ownership does not moderate the capital structure to the value of the firm. Managerial ownership does not moderate intangible assets to the value of the company. Capital structure and intangible assets affect the value of the company.